PENGARUH SUASANA TOKO DAN LOKASI TERHADAP NIAT BELI ULANG KONSUMEN DI MINIMARKET SEKAWAN TABANAN - Apriliani, Ni Putu Dessy Ari; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 4 No 2 (2015), 2015)
The purpose of this study is to examine and analyze the effect of (1) store atmosphere to the consumer re-purchase intention, (2) location of the consumer re-purchase intention in Minimarket Sekawan Tabanan. The number of samples taken were 112 respondents using purposive sampling technique. D ata analysis technique used is multiple linear regression analysis. R esults showed that atmosphere of departure and the location has a significant influence on consumer purchase intentions Minimarket Sekawan . As well as the atmosphere of the store and the location of a significant effect on purchase intentions re simultaneously.
Keywords: suasana toko, lokasi, niat beli ulang konsumen